2023
DOI: 10.3390/info14010031
|View full text |Cite
|
Sign up to set email alerts
|

Smart Platform for Data Blood Bank Management: Forecasting Demand in Blood Supply Chain Using Machine Learning

Abstract: Despite the efforts of the World Health Organization, blood transfusions and delivery are still the crucial challenges in blood supply chain management, especially when there is a high demand and not enough blood inventory. Consequently, reducing uncertainty in blood demand, waste, and shortages has become a primary goal. In this paper, we propose a smart platform-oriented approach that will create a robust blood demand and supply chain able to achieve the goals of reducing uncertainty in blood demand by forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
(46 reference statements)
0
2
0
Order By: Relevance
“… 36 , 37 Similarly, in a study of Chilean blood donors, it was concluded that blood donors who had previously donated blood were more likely to dominate in future donations. 38 …”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Similarly, in a study of Chilean blood donors, it was concluded that blood donors who had previously donated blood were more likely to dominate in future donations. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The medical community is focusing on strengthening supply networks to reduce risks and waste while maintaining customer service standards [ 1 , 2 ]. The main challenges in the health supply chain include demand uncertainty, inventory management, expiration, and a lack of resources [ 2 , 3 , 4 ]. Planning blood collection and distribution is crucial for hospitals and healthcare facilities, especially in the production and distribution of various blood components.…”
Section: Introductionmentioning
confidence: 99%
“…Planning blood collection and distribution is crucial for hospitals and healthcare facilities, especially in the production and distribution of various blood components. Forecasting blood consumption ensures balance between demand and supply, preventing inventory shortages or oversupply [ 4 ]. This allows for rational resource allocation and clinical need coordination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations